Funktionelle Defizite und Selbsteinschätzung der Leistungsfähigkeit nach chirurgischer Hüftluxation - Luder, Gere; Bertschy, Bettina; Rocourt, Marianne HH; Deschner, Gabriela; Radlinger, Lorenz (Sportverletzung · Sportschaden, 2011)
Background: Surgical hip dislocation (SHD) is a common procedure to treat several hip prob-lems, namely femoroacetabular impingements. After surgery patients are required to walk with reduced weight-bearing for six to eight weeks. The literature describes important changes in general health and functional state after immobilization but little is known about physical and functional recovery of these deficits. The aim of the study was to investigate the condi-tional deficits and changes of patients 3 and 12 months after SHD, and to compare them to healthy subjects. Materials and Methods: A prospective cross-sectional study with three groups was performed: 29 patients 3 months after SHD (G3), 28 patients 12 months after SHD (G12) and 34 healthy persons (G0). Strength, endurance, gait, stair climbing and balance were measured and self-perceived performance and satisfaction with daily-life activities was evalu-ated with questionnaires. Group differences were tested with Kruskal-Wallis test and post-hoc with the Mann-Whitney U test. Results: Significant differences were found for G3 compared to G0 in strength and endurance parameters, as well as for gait and self-perceived perform-ance. G12 also showed significant differences compared to G0 and only little differences were found compared to G3. Conclusion: The remaining deficits in patients twelve month after SHD with regard to conditional and functional parameters indicate that full recovery for ac-tivities of daily life has not been achieved by these patients. A specific therapy program may be able to improve the patient’s strength, endurance and functional performance and may pos-sibly lead to effective protection of the joint and enhanced performance in daily life.
Keywords: Background; Materials und Methods; Results; Conclusion